Linking strategies and biases when matching cohorts to the National Pupil Database. (2017) - Downs, Johnny; Setakis, Efrosini; Mostafa, Tarek; Hayes, Richard; Hotopf, Matthew; Ford, Tamsin; Gilbert, Ruth
No abstract available